Are startups doing what they believe is important? - Halili, Ylldrin (My University, 2017)
The lean startup methodology has become popular amongst entrepreneurs, professionals and scholars, and some of the world’s leading business schools and startup accelerators are using it today for their entrepreneurship programs. However, these principles do not touch psychological factors that have been proven important for teams in order to be creative and innovative. This study was done since it was deemed interesting to see if there is a discrepancy in what of the above mentioned that startups believe is important for their future success, and to what degree they actually practice it. In order to investigate the discrepancies, a framework consisting of in total 25 innovation psychology and lean startup methodology theory groups was built. The relevant theories, were identified after a literature review and ten interviews with startup founders. In an iterative manner, 25 statements for a survey were created based on the theory groups. Survey respondents had to rate the importance and the agreement for every statement. The sampling for the startups participating in the survey was delimited to Swedish startups due to the short time limit for the study and the lack of personal network of startups abroad. The study was further limited by only having one startup accelerator participating; the other startup accelerator did not manage to reach out to its startups in time. However, due to the sample size, the wide array of fields for the startups participating, and the relatively low spread of the answers, the author is confident that the findings can be generalizable to Swedish startups in general. The findings show that the average discrepancy for startups is -9.80%, which can be considered low. This result indicates that startups are much better than large companies at practicing what they perceive is important for their future success. Furthermore, startups seem to have a propensity for practicing the factors that can be derived from innovation psychology. The factors derived from the lean startup methodology are not practiced to the same extent. Moreover, attempts have been made to create profiles regarding the startups surveyed. These are hypotheses based on the responses that have stuck out in the survey and should be tested in the future. To conclude, a future study should look into which of the IPLSM factors correlate to successful performances for startups.
Keywords: Innovation och entreprenörskap (nyttiggörande); Övrig annan teknik; Innovation & Entrepreneurship; Other Engineering and Technologies not elsewhere specified